Correlation of GRP and socio-economic indicators - E. D. Butenko; E. A. Kutko (Вестник Северо-Кавказского федерального университета, 2023)
Regions with high incomes have free funds to develop digitalization and maintain the achieved level of digital development. Nevertheless, digital technologies can become helpful for regions with not so high GRP, such as the Tyumen Region, Leningrad Region and Chelyabinsk Region. They were able to firm the conditions for digital growth. In our opinion, this is due to the peculiarities of the regions as the industry developed in the regions under consideration provided the foundation for the development of the digital component since the first automated control systems were the progenitors of digital technologies. As a result, the correlation between the level of GRP and the digital development index was revealed. The article examines GRP indicators of the regions of the Russian Federation (leaders and outsiders) and assesses their socio-economic context. The relevance of this topic is due to the fact that life expectancy of the population is influenced by a large number of factors of a different nature. In this regard, in our country with high regional differentiation both in terms of climatic and socio-economic living conditions of the population, their analysis based on state statistics is of great practical importance. The socio-economic “indicator of the standard of living of the population” is used in the scientific sources, in legislative and legal documents to assess the degree of satisfaction of the physiological, personal and social needs of people in society. The issue is topical since the results obtained from the analysis of socio-economic development data can be used to develop provisions for improving the standard of living of the population in different regions of the country.